Establishment of Laneleaf Tickseed (Coreopsis lanceolata) in Roadside Right-of-Ways - Jeffrey G. Norcini; Anne L. Frances; Carrie Reinhardt Adams (EDIS, 2009)
ENH-1103, an 8-page illustrated fact sheet by Jeffrey G. Norcini, Anne L. Frances, and Carrie Reinhardt Adams, provides recommendations for establishing northern-Florida ecotypes of this low-growing, short-lived perennial that blooms with yellow flowers in early to mid-spring, including site selection, site preparation, sowing seeds, establishment, and maintenance. Includes references. Published by the UF Department of Environmental Horticulture, March 2009.